The Interaction of 2D Materials With Circularly Polarized Light. Issue 10 (25th January 2023) - Rong, Rong; Liu, Ying; Nie, Xuchen; Zhang, Wei; Zhang, Zhuhua; Liu, Yanpeng; Guo, Wanlin
Abstract: 2D materials (2DMs), due to spin‐valley locking degree of freedom, exhibit strongly bound exciton and chiral optical selection rules and become promising material candidates for optoelectronic and spin/valleytronic devices. Over the last decade, the manifesting of 2D materials by circularly polarized lights expedites tremendous fascinating phenomena, such as valley/exciton Hall effect, Moiré exciton, optical Stark effect, circular dichroism, circularly polarized photoluminescence, and spintronic property. In this review, recent advance in the interaction of circularly polarized light with 2D materials covering from graphene, black phosphorous, transition metal dichalcogenides, van der Waals heterostructures as well as small proportion of quasi‐2D perovskites and topological materials, is overviewed. The confronted challenges and theoretical and experimental opportunities are also discussed, attempting to accelerate the prosperity of chiral light‐2DMs interactions. Abstract : The interaction between 2D materials and circularly polarized light (CPL) provides an attractive control knob for investigating emergent exotic phenomena, especially for chiral‐electronics, photonics, and optoelectronics effects. This review summarizes exciting chiral light‐induced phenomena in representative 2DMs, covering from distinct interaction mechanisms, advances, faced challenges and perspectives, attempting to boost tremendous applications in future optoelectronics, spintronics, and valleytronics.